(untitled) - Pinchover, Yehuda (Cambridge, UK, 2005)
A complete introduction to partial differential equations, this textbook provides a rigorous yet accessible guide to students in mathematics, physics and engineering. The presentation is lively and up to date, paying particular emphasis to developing an appreciation of underlying mathematical theory. There is a rich collection of worked examples and exercises to accompany the text, along with a large number of illustrations and graphs to provide insight into the numerical examples.
Keywords: Differential equations, partial; Textbooks